VD_FINDINFO Jug / 2014 / 336 vom 6. März 2015 - VD Tribunal cantonal (2015)
COURTAGE, LÉGITIMATION ACTIVE ET PASSIVE, CONCURRENCE DÉLOYALE, MODIFICATION DE LA DEMANDE | 18 al. 1 CO, 18 CO, 412 al. 1 CO, 412 CO, 266 al. 1 CPC, 266 CPC, 268 al. 1 CPC, 268 CPC, 2 LCD, 5 LCD, 5 let. a LCD, 9 al. 1 LCD, 9 al. 3 LCD, 9 LCD